2015
DOI: 10.1159/000368653
|View full text |Cite
|
Sign up to set email alerts
|

E-Learning in Urology: Implementation of the Learning and Teaching Platform CASUS® - Do Virtual Patients Lead to Improved Learning Outcomes? A Randomized Study among Students

Abstract: Background: E-learning is playing an increasing role in medical education, supporting a problem-based and practical oriented education without putting patients at risk and compensating for the decrease in instructor-centered teaching. Not much research has been done concerning learning effects and reaction on behalf of the students. Methods: We created computer-based cases for four important diagnoses in urology using the authoring system CASUS®. Fourth-year medical school students were randomized into two gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 12 publications
1
18
0
Order By: Relevance
“…eBooks can provide additional independent directed interactive learning outside the classroom. There is a great deal of literature emphasizing the role of technology and how it can be used as a complementary resource [9, 11, 1619]. The authors suggest that eBooks have a place in reducing teaching load and expense when used as an adjunct to traditional methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…eBooks can provide additional independent directed interactive learning outside the classroom. There is a great deal of literature emphasizing the role of technology and how it can be used as a complementary resource [9, 11, 1619]. The authors suggest that eBooks have a place in reducing teaching load and expense when used as an adjunct to traditional methods.…”
Section: Discussionmentioning
confidence: 99%
“…Schneider et al created computer-based cases for important diagnoses in urology using the authoring system CASUS® [9]. They found that members of the CASUS® group using the online cases for preparation scored significantly higher with an average of 20% better test results than students using textbooks for preparation.…”
Section: Introductionmentioning
confidence: 99%
“…Further in regard to specialty studies (e.g. urology courses) it is reported that students using the e-learning environment prior to taking exams scored higher than students using textbooks only (20% better results) ( 14 ). Results therefore indicated that there was a benefit to learning using virtual patients, yet it had to be further explored as to what this benefit is attributed to and how to best exploit it.…”
Section: Discussionmentioning
confidence: 99%
“…That would also better organize students’ course work. As an effect of these student perceptions there should also be better educational outcomes gained ( 12 , 13 , 14 ). It is now important to evaluate those changes in further research to understand the influences of such study settings for multifactorial learning as is present in family medicine.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of guidelines and problem-based e-learning plus interaction with the computer increases knowledge and results in change in practice [8]. Schneider et al stated that students using the learning and teaching platform CASUS ® for preparing lectures of VPs lead to improved outcomes [9]. The students perceive the e-learning courses as very useful if the access is simple and the contents are meaningful with assessments and feedback.…”
Section: Students' Perspectivementioning
confidence: 99%